Anemia among HIV‑positive women in LMICs: Multilevel analysis of recent DHS survey - Enyew Getaneh Mekonen (PLoS ONE, 2026)
Introduction Anemia affects over 30% of women of reproductive age globally, with the highest burden in low‑ and middle‑income countries, and it poses additional risks for women living with human immunodeficiency virus (HIV), including disease progression and reduced survival. Although previous studies report prevalence among HIV‑positive women ranging from 37.8% to 55.8%, most evidence comes from hospital‑based or high‑income settings, leaving a gap in population‑level data. Addressing this gap is critical, as women in low- and middle-income countries (LMICs) often face overlapping vulnerabilities such as nutritional deficiencies, limited healthcare access, and high HIV burden. Using nationally representative Demographic and Health Surveys, this study aims to estimate anemia prevalence and identify associated factors among HIV‑positive women to inform targeted interventions and integrated management strategies. Methods A cross‑sectional study was conducted using Demographic and Health Survey data collected between 2022 and 2024 from nine countries in sub-Saharan Africa and Asia, including 1,446 HIV‑positive women aged 15–49 years. Hemoglobin concentration was used to classify anemia based on World Health Organization (WHO) thresholds. Individual and community‑level factors were examined, and weighted data were analyzed using multilevel logistic regression to account for clustering. Associations were reported as adjusted odds ratios with 95% confidence intervals. Results Among HIV‑positive women in Africa and Asia, the prevalence of anemia was 50.62% (95% confidence interval (CI): 48.04–53.20%), with 19.29% classified as mild, 26.28% as moderate, and 5.05% as severe. Prevalence varied widely across countries, ranging from 71.43% in Mali to 12.00% in Tajikistan. Educational status [adjusted odds ration (AOR) = 0.43; 95% CI: 0.22–0.81], media exposure [AOR = 0.41; 95% CI: 0.19–0.87], contraceptive use [AOR = 2.37; 95% CI: 1.35–4.17], and iron supplementation during pregnancy [AOR = 2.17; 95% CI: 1.04–4.55] were significantly associated with anemia. Conclusions Anemia remains a major public health concern among HIV‑positive women, driven by reproductive, nutritional, and socio‑behavioral factors. Strengthening antenatal and HIV care programs, integrating family planning services, and promoting adherence to iron supplementation are critical strategies to reduce anemia risk. Tailored health communication and nutritional interventions, alongside future longitudinal studies, are essential to establish causal pathways and inform targeted interventions.